Spatial distribution of plasma density and magnetic field amplitude in the dayside magnetosheath as a function of the IMF orientation - Michotte de Welle, B.; Aunai, N.; Lavraud, B.; Génot, V.; Jeandet, A.; Nguyen, G.; Ghisalberti, A.; Smets, R. (Frontiers in Astronomy and Space Sciences, 2024)
The properties of the magnetosheath are of pivotal importance in determining the coupling between the magnetosphere and interplanetary medium. In particular, the magnetic flux pileup and plasma depletion layer (PDL) modify the boundary conditions of magnetopause reconnection. However, the spatial distribution of the magnetic field strength and plasma density in the magnetosheath and their functional dependence on the interplanetary magnetic field (IMF) orientation remain poorly understood. This study characterizes these aspects in detail through the statistical processing of decades of data from Cluster, Double Star, THEMIS, and Magnetospheric Multiscale (MMS) missions. The first part of this study focuses on the poorly known variations across the magnetosheath, from the shock to the magnetopause. The magnetic pileup and PDL are significantly correlated, with a strong dependence on the IMF cone angle. Their dependence on the IMF clock angle is found only near the magnetopause, consistent with the expected effect of magnetic reconnection. The second part of this study examines the asymmetry in the magnetic field amplitude and density between the quasi-parallel and quasi-perpendicular sides of the equatorial magnetosheath. These asymmetries are characterized for different relative distances to the magnetopause and bow shock boundaries and for different IMF orientation. The magnetic field amplitude, observed to be higher on the quasi-perpendicular side of the magnetosheath, becomes more symmetric as it approaches the magnetopause. The quasi-parallel magnetosheath exhibits a higher plasma density near the magnetopause. However, this asymmetry reverses at approximately the mid-magnetosheath with a decreasing IMF cone angle.